STUDI PERSYARATAN TANGGA DARURAT PADA RUMAH TOKO DI SURABAYA - Mariska, Imanto E.; Indrani, Hedy C. (Dimensi Interior, 2010)
A shop-house is a simple and practical alternative residential space that can accommodate various activities from small economic scale to the combination of living and working functions. This triggers the uncontrolled development of shop-house construction so as to meet the increasing demands of users. The demand of short-time construction has caused the shop-houses to be constructed poorly with low considerations to safety, adding to misuse. This has caused fire cases in the shop-houses sacrificing many lives who were unable to evacuate from the building. Using the qualitative and descriptive method of research, this research aims to provide solutions and alternative emergency staircase designs appropriate for shop-houses in Surabaya to increase the safety of the users